RISK ANALYSIS OF BULK LPG DISTRIBUTION IN WEST NUSA TENGGARA PROVINCE WITH HOUSE OF RISK AT INDONESIA OIL AND GAS COMPANY REGIONAL JATIMBALINUS - Cucuk Basuki; Iwan Vanany (Green Publisher, 2023)
Since 2007, the Indonesian government has started a program to convert kerosene to Liquid Petroleum Gas (LPG). Over time, the use of LPG is one of the primary needs that must be met. Besides that, Company X as oil and gas company follows the Indonesian government regulations regarding the COVID-19 restriction which in this case it will add to the increasingly complex problems of the supply chain network. This is what makes bit a challenge for Company X to meet consumer needs with the availability of existing LPG. This causes the risks that demand for LPG cannot be fulfilled on certain days because the number of requests is greater than the amount of supply. In this study, a house of risk was conducted in Company X’s bulk LPG supply chain. The results of this study produce risks, causes of risk along with comprehensive prevention strategies to help Company X supply chain complexity